Rare case of a granulocytic sarcoma: cytological evaluation - Mahadani, Jayawant; Chide, Pratik; Khandekar, Sanjay; Khandekar, Hitendra; Lodha, Nilima; Raut, Vaman; Hingway, Snehalata (International Journal of Research in Medical Sciences, 2016)
Granulocytic sarcomas (chloromas) are rare extramedullary tumors consisting of primitive granulocytic cells. They arise de novo, or are associated with other hematologic disorders such as acute myeloid leukemia, myelodysplastic syndrome, or myeloproliferative disorders. We report here a case of a 33-year-old man who presented with extensive skin lesions all over body, including face region. The patient is a known case of chronic myeloid Leukemia (CML). Fine needle aspiration cytology (FNAC) of skin lesion was suggestive of granulocytic sarcoma. Histological evaluation of skin biopsy revealed infiltration by atypical myeloid cells. Peripheral blood smear (PBS) examination was within normal limit. Immunohistochemistry (IHC) confirmed the diagnosis of Granulocytic sarcoma. Here we present a case of granulocytic sarcoma which was suspected on FNAC findings and which was confirmed on histochemistry and immunohistochemistry. These cases illustrate the utility of FNAC in diagnosis of granulocytic sarcoma.